2011
DOI: 10.1074/jbc.m110.189183
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Biochemical Mechanism Underlying the Influence of Sterol Deprivation Stress on Caenorhabditis elegans Longevity

Abstract: To investigate the biochemical mechanism underlying the effect of sterol deprivation on longevity in Caenorhabditis elegans, we treated parent worms (P0) with 25-azacoprostane (Aza), which inhibits sitosterol-to-cholesterol conversion, and measured mean lifespan (MLS) in F2 worms. At 25 M (ϳEC 50 ), Aza reduced total body sterol by 82.5%, confirming sterol depletion. Aza (25 M) treatment of wild-type (N2) C. elegans grown in sitosterol (5 g/ml) reduced MLS by 35%. Similar results were obtained for the stress-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…Although C. elegans lack de novo cholesterol biosynthesis, they require cholesterol for germ cell development, growth, stress resistance, dauer formation, fat storage, cuticle formation, and modulation of other lipids [7, 9, 10, 4850]. Changes in exogenous or endogenous cholesterol profoundly affect C. elegans cellular function and cholesterol cannot be replaced by other lipid molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although C. elegans lack de novo cholesterol biosynthesis, they require cholesterol for germ cell development, growth, stress resistance, dauer formation, fat storage, cuticle formation, and modulation of other lipids [7, 9, 10, 4850]. Changes in exogenous or endogenous cholesterol profoundly affect C. elegans cellular function and cholesterol cannot be replaced by other lipid molecules.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SREBP and LXR are transcription factors that regulate the expression of genes involved in cholesterol homeostasis [1, 2], lipoproteins and NPCs are transporters of cholesterol, and caveolin located in the membrane regulates both cholesterol transport and signal transduction [35]. As in mammals, cholesterol in Caenorhabditis elegans has diverse functions [69] including an interaction with the insulin signaling pathway [10, 11]. A key difference between worms and mammals, however, is that worms require only a very small amount of cholesterol, suggesting that cholesterol primarily functions in signaling.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that glucose diet reduces the lifespan of C. elegans through repressing the activity of transcription factors involved in extending lifespan [ 18 ]. Such transcription factors are inactivated by insulin signaling executed by DAF-16 and HSF-1 [ 22 , 23 ]. The level of insulin in the blood increases quickly after intake of high glucose foods and then decreases soon thereafter, making insulin a potent mediator of the effects of high glucose diets on aging in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the paths examined intersect on the transcription factor skn-1 , shown to inhibit one of insulin-like peptides ( ins-7 ) 33,61 and skn-1 suppression coupled with a daf-28 induction has been suggested as a negative transcriptional feedback. 62 Furthermore, both ins-7 and daf-28 were found to be up-regulated in 2 of the experiments, i.e. rheb-1 i and let-363 i.…”
Section: Resultsmentioning
confidence: 89%